(untitled) (Washington, DC, 2006)
This is a critical period for the WTO and for realizing the potential of trade as a driver of growth and poverty reduction. It is time for good intentions to be translated into solid multilateral agreements that promote development, and it is high time that the rich countries tore down their barriers. But trade agreements by themselves cannot guarantee growth and poverty reduction: aid for trade and internal reforms are needed too. On all this, detail matters and trade agreements are complex. This book provides an up-to-date, clear, and thoughtful analysis of these crucial issues.
Keywords: Economic development,Economic policy,International economic relations,Phát triển kinh tế,Quan hệ kinh tế quốc tế,Chính sách kinh tế